MORALITAS DALAM NOVEL BIDADARI-BIDADARI SURGA KARYA TERE LIYE - Odi Satri Permana; Nurizzati Nurizzati; Bakhtaruddin Nasution (Faculty of Languages and Arts, Universitas Negeri Padang, 2014)
This study aimed to describe the morality of the characters in the novel Angels-Angels Heaven works Tere Liye. Morality is described that relate to conscience, freedom and responsibility, values ​​and norms, as well as the rights and obligations of the characters in the novel. To determine morality contained in the novel then used the following research questions: How moralitastokoh-figure-terdapatvdalam novel Angel Angel Heaven Tere Liye work, in terms of morality, namely: conscience, freedom and responsibility, values ​​and norms, as well as the rights and obligation This type of research is qualitatively using descriptive content analysis (content analysis). This method is used to see and describe the existing data in novel Angel Angel-Heaven Work Tere Liye which decomposes in the form of words rather than in the form of numbers. In the data collection was done in three steps: read and understand the novel Angel-Angel Heaven TereLiye work, mark events and figures behavioral symptoms that lead to focused research, and inventory data by using the format of the data inventory. Results of this study showed that the novel Angel Angel Heaven-there character who has morality associated with (1) conscience, which is reflected by the figures, namely: Laisa figures, figures Dalimunte, Ikanuri figures, figures Wibisana, Yashinta figures; (2) freedom and responsibility, reflected by the figures, namely: laisa figures, figures Dalimunte, Mamak Lainuri figures, and figure Burhan Wak, (3) values ​​and norms, reflected by the figures, namely: Ikanuri figures, figures Wibisana; (4 ) the rights and obligations reflected by figures, namely: Laisa figures, figures mamak Lainuri.